Measurement of public awareness of climate change in China: based on a national survey with 4, 025 samples. Issue 4 (2nd October 2017) - Wang, Binbin; Shen, Yating; Jin, Yangyang
ABSTRACT: Just before the new round of UN climate change conference in Bonn, a survey report, named as the Climate Change in the Chinese Mind 2017, was released in Beijing. The investigation was conducted in the form of a computer-assisted telephone survey with a sample size of 4, 025 samples, covering 332 prefecture-level administrative units and four municipalities in China. Urban-rural proportion and sex proportion were specially taken into account, so as to demonstrate the Chinese public awareness objectively. The investigation measures the public awareness from six aspects, which includes climate change beliefs, impacts, response, policies, actions, and the assessment of the effectiveness of climate communication. This article presents the key findings of the survey and provides further insights behind the data.